Hubungan Antara Welas Diri Dengan Tingkat Kesejahteraan Psikologis Ibu Postpartum Di Kabupaten Pekalongan - Dina Ulya; Ratnawati Ratnawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Psychological changes in postpartum mothers often show uncertain emotions after giving birth, especially sadness and irritability. These psychological problems can be faced by postpartum mothers by cultivating psychological well-being. One way to improve the psychological well-being of postpartum mothers is by cultivating a self-compassionate attitude to reduce symptoms of depression, anxiety and worry in order to achieve the psychological well-being of postpartum mothers. This research aims to determine the relationship between self-compassion and the level of psychological well-being of postpartum mothers in Pekalongan Regency. This research uses descriptive correlation with a cross sectional approach. The samples taken using a purposive sampling technique were 79 postpartum mothers in Pekalongan Regency. Data were collected using the Self-Compassion Scale (SWD) questionnaire & Psychological Well-Being questionnaire. Data analysis used the Spearman rank test. This research showed that there were 53 people experiencing high self-compassion (67.1%), and 46 people with low psychological well-being (58.2%). The results of the analysis show that there is a relationship between self-compassion and the level of psychological well-being of postpartum mothers, P value = 0.000 (p <0.05). The conclusion of this research is that there is a relationship between self-compassion and the level of psychological well-being of postpartum mothers in Pekalongan Regency. From these results it is hoped that nurses can help improve self-compassion and psychological well-being of postpartum mothers by means of health education.